2017
DOI: 10.1177/1477370816640136
|View full text |Cite
|
Sign up to set email alerts
|

Framing migration and the process of crimmigration: A systematic analysis of the media representation of unauthorized immigrants in the Netherlands

Abstract: In this article we examine whether the proposal to criminalize illegal stay in the Netherlands was preceded by increased negative media attention for unauthorized immigrants. Using a corpus linguistics approach, we carried out a quantitative discourse analysis of all newspaper articles on unauthorized migrants over a period of 15 years. Our results show that the amount of media coverage actually strongly decreased in the years before the proposal, and this coverage was moreover increasingly less negative. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 63 publications
5
31
1
3
Order By: Relevance
“…We found that otherness is delineated when an attempt is made to exclude and distance the dominant, acceptable behavior from that of the migrant who transgresses against the wall in his or her actions. This is emphasized through verbs that strengthen the idea of contrast, collision and a certain level of violence, such as plot, bust into, sneak and smuggle , and labels that explicitly criminalize human mobility behaviors, such as criminal, dangerous, invaders, lunatics, non-citizens, not asylum seekers , supporting other studies that have found similar strategies in immigration representations (Brouwer et al, 2017; Clark-Ibanez and Swan, 2019; Dunaway et al, 2011; Figenschou and Thorbjørnsrud, 2015; Horsti, 2007). This emphasis on behaviors and labels focused on illegality have also been found to be classic, straightforward strategies used to imply otherness (Greer and Jewkes, 2005), and establish migrants as a threat (Jengelley and Clawson, 2019).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…We found that otherness is delineated when an attempt is made to exclude and distance the dominant, acceptable behavior from that of the migrant who transgresses against the wall in his or her actions. This is emphasized through verbs that strengthen the idea of contrast, collision and a certain level of violence, such as plot, bust into, sneak and smuggle , and labels that explicitly criminalize human mobility behaviors, such as criminal, dangerous, invaders, lunatics, non-citizens, not asylum seekers , supporting other studies that have found similar strategies in immigration representations (Brouwer et al, 2017; Clark-Ibanez and Swan, 2019; Dunaway et al, 2011; Figenschou and Thorbjørnsrud, 2015; Horsti, 2007). This emphasis on behaviors and labels focused on illegality have also been found to be classic, straightforward strategies used to imply otherness (Greer and Jewkes, 2005), and establish migrants as a threat (Jengelley and Clawson, 2019).…”
Section: Discussionsupporting
confidence: 73%
“…In terms of the characterization of migrants, the current US administration has deepened a climate of political polarization by referring to any action by immigrants as illegal (Holpuch, 2019). This aligns with a solid body of research that supports the idea that mainstream media and dominant discourse from political figures have traditionally portrayed immigrants in a frame that focuses excessively on the illegality factor (Brouwer et al, 2017; Clark-Ibanez and Swan, 2019; Dunaway et al, 2011; Figenschou and Thorbjørnsrud, 2015; Horsti, 2007).…”
Section: Introductionsupporting
confidence: 68%
“…of human smuggling). Some scholars label such frame as the illegality frame (Horsti, 2007; McKay et al., 2011) and others use the concept of criminalization or criminality (Breen et al., 2006; Brouwer et al., 2017; Greussing and Boomgaarden, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This may raise concerns about arbitrariness. To avoid this, some researchers applied a computer-assisted approach to frame analysis, sometimes combined with a linguistic approach (Brouwer et al., 2017; Lawlor and Tolley, 2017). These studies identified the frames either on the basis of emerging word clusters (Greussing and Boomgaarden, 2017) or specific linguistic relations between words (Blinder and Allen, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, Sub-Saharan women are linked to prostitution (Fabini, 2017), while Eastern Europeans are associated with violent crimes, and North Africans to drug trafficking (De Giorgi, 2010). And in the Netherlands, anti-immigrant narratives largely determined national elections, ultimately cementing anti-Muslim sentiments and links between criminality and immigration (Brouwer, van der Woude, & van der Leun, 2017;van der Woude et al, 2014).…”
Section: The Globalization Of Crimmigrationmentioning
confidence: 99%